March to the majority : the real story of the Republican revolution - Gingrich, Newt; Gaylord, Joe; Brogdon, Louie (Center Street, 2023)
Gingrich, Gaylord and Brogdon take readers behind the scenes of the Republican revolution in 1994, and the rise of the modern GOP. They share never-before-told stories about Ronald Reagan, Richard Nixon, and other fascinating political figures. They also show how the rise of modern conservatism is immensely relevant today in dealing with the challenges our nation faces. -- adapted from jacket